The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/ppe.12012
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilisation in the First Year of Life Among Infants of Mothers With Perinatal Depression or Anxiety

Abstract: Background-Limited information is available on associations between maternal depression and anxiety and infant health care utilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 19 publications
3
65
0
Order By: Relevance
“…Lansakara et al [56] reported that 97 % of women had contact with a primary health care practitioner, either GP or CFH nurse with regard to their own health at least once during the first three months postpartum, and most (approximately 75 %), contacted both of these professionals at least once in first three months. Farr et al [57] also reported that infants of mothers with perinatal depression or anxiety were as likely to attend well baby visits and receive immunisations as their counterparts. This reinforces the importance of generalist health professionals and those providing universal CFH services taking the opportunity to inquire sensitively about the social and emotional health of pregnant women and parents with young infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lansakara et al [56] reported that 97 % of women had contact with a primary health care practitioner, either GP or CFH nurse with regard to their own health at least once during the first three months postpartum, and most (approximately 75 %), contacted both of these professionals at least once in first three months. Farr et al [57] also reported that infants of mothers with perinatal depression or anxiety were as likely to attend well baby visits and receive immunisations as their counterparts. This reinforces the importance of generalist health professionals and those providing universal CFH services taking the opportunity to inquire sensitively about the social and emotional health of pregnant women and parents with young infants.…”
Section: Discussionmentioning
confidence: 99%
“…They may be less likely to have a regular GP and use ED instead. Farr et al [57] also found that infants of mothers with prenatal and postpartum depression or anxiety were more likely to have ≥6 sick/emergency visits than infants whose mothers did not have PMH problems. Chee et al [58] similarly reported that women who had brought their infants for three or more non-routine visits to the infant’s doctor had a significantly higher prevalence of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is some evidence that untreated postpartum mood disorders can contribute to higher rates of physical illness and hospitalization among infants. For instance, a study of 24,263 infants born between 1998 and 2007 showed that infants of mothers who were diagnosed with perinatal anxiety or depression were seen more often for ear infections, respiratory infections, and injury compared to infants of mothers without depression and anxiety (Farr et al 2013). Thus, early intervention for postpartum mood disorders has the potential to improve outcomes for both mothers and their children.…”
mentioning
confidence: 98%
“…Some studies have investigated postnatal depression or anxiety and healthcare utilization in infants, with no difference in health-care utilization within the first 14 days post-birth (Paul et al 2013), and in preventative health-care services up to 1 year (Farr et al 2013). However, infants of mothers with depression or anxiety diagnosed during the postpartum period had more emergency visits than infants of mothers with no depression or anxiety (Farr et al 2013). Due to the smaller sample size, we may have been unable to detect differences in healthcare utilization in infants.…”
Section: Discussionmentioning
confidence: 99%